A critical biocultural approach to early growth in the United States. Issue 6 (5th February 2022) - Miller, Elizabeth M.
Abstract: Objectives: A critical biocultural anthropology seeks to link perspectives from social theory and ethnography to human biology. In the United States (U.S.), multiple forms of structural inequalities affect early growth, including racism and poverty. The goal of this paper is to test the effects of social inequalities on birth weight and later height in the U.S. National Health and Nutrition Survey (NHANES), and to contextualize potential pathways of embodiment that link social structure and biology. Methods: This study used data from 8392 children ages 0–5 years from the 2005 to 2016 NHANES. Reported birth weight and measured length/height (converted to height‐for‐age z‐scores) were used as outcome variables, while various measures of socioeconomic status and the NHANES‐defined race and ethnicity categories were operationalized as social variables. Structural equation modeling (SEM) was chosen to represent the data. Results: The final model represented an excellent fit to the data. Higher birth weights were associated with higher height‐for‐age z‐scores. The Black racial category was associated with lower birth weight and higher height‐for‐age z‐score, while the "Other" racial category was also associated with lower birth weight. The socioeconomic status factor variable was significantly associated with birth weight and height‐for‐age z‐scores. There were also multiple indirect effects of social variables on height‐for‐age z‐scores mediated via their effects on birth weight. Conclusions: Inequalities in race and socioeconomic status persist in birth weight and early childhood stature in the U.S. These findings can be contextualized by a critical biocultural anthropology that integrates lived experiences and pathways of embodiment.